Beyond Technical Skills: Digital Competence in In-Service Training for Islamic Religious Education Professional Teachers - Ritonga, Asnil Aidah; Khadijah; Harahap, Fikrah Elhifzi (Jurnal Pendidikan Agama Islam, 2026)
Purpose – This study examines how generic, didactic, and professional digital competence are enacted in in-service Islamic Religious Teacher Professional Education programs at Islamic universities in Indonesia, and how institutional demands, infrastructural constraints, and value-oriented aims shape digital teaching practices. Design/methods/approach – A multi-site qualitative case study was conducted across three Islamic universities in Sumatra, Indonesia. Data from 15 participants including programme coordinators and lecturers in in-service IRE teacher training were collected via interviews, focus groups, observations, and document analysis, and analysed thematically using a hybrid inductive–deductive approach in ATLAS.ti, followed by within- and cross-case analysis Findings – The findings show that digital competence was enacted primarily as a situated and adaptive professional practice rather than as a transformative pedagogical capacity. Four interrelated themes emerged: (1) digital competence as operational survival rather than pedagogical redesign, (2) didactic competence as adaptive practice under infrastructural and organisational constraint, (3) professional competence as pedagogical judgement under constrained autonomy, and (4) pedagogical disposition as a mediator of engagement, ambivalence, and resistance toward digital teaching. Across institutional contexts, lecturers mainly utilised digital platforms to sustain instructional continuity and fulfil programme requirements, while dialogical interaction, formative feedback, and pedagogical redesign remained limited. Research implications/limitations – This study shows that strengthening digital competence in Islamic teacher education requires more than technical training or platform adoption, relying on institutional support, pedagogical redesign, professional autonomy, and context-sensitive development to enable meaningful digital pedagogy in value-oriented settings. It is limited to three Islamic universities in Sumatra and focuses on lecturers’ perspectives in in-service IRE teacher training programs. Originality/value – This study reframes digital competence in Islamic teacher education as an enacted, relational, and institutionally mediated practice, rather than a purely technical or individual capacity, situating it within the pedagogical, ethical, and organizational contexts of Islamic Religious Education teacher preparation.